Exposure to the advertisement of toombak at the point-of-sale among adolescents in Khartoum State, Sudan: A crosssectional study - Hatim M. Almahdi (Tobacco Prevention and Cessation, 2020)
Introduction This study aimed to assess the association between toombak (smokeless tobacco) advertisement at point-of-sale (PoS) and its use among adolescents in Sudan.